Khả năng ức chế ăn mòn thép cacbon của nano oxit kẽm biến tính với axit 2-benzothia-zoylthio-succinic - Trúc, Trịnh Anh; Thắng, Đặng Quyết; Vũ, Phạm Gia; Xuân Hằng, Tô Thị (Vietnam Journal of Chemistry, 2015)
In this study, ZnO nanoparticle was synthesized and modified by a corrosion inhibitor 2-benzothiazolylthio-succinic acid (BTSA) for corrosion protection of a carbon steel surface. The TEM, SEM and IR analyses were used for characterized the synthesized products. The nano ZnO size in the about 20 nm and the IR analyze shows the presence of BTSA on the ZnO surface. The corrosion inhibition of nano ZnO and nano ZnO bearing BTSA in the NaCl 0.1 M solution was characterized using electrochemical techniques. In the NaCl 0.1 M, both nano ZnO and nano ZnO-BTSA have the inhibition property for carbon steel surface. The inhibition efficiency of ZnO-BTSA is higher than of pure ZnO. The polarization curves indicate that ZnO is anodic inhibitor while the ZnO-BTSA is a mixed-type inhibitor.